Kajian Cekaman Kekeringan Sesudah Masa Berbunga Tanaman Kacang Merah (Phaseolus vulgaris L.) pada Tanah Entisol - Apriana Hoar Seran; Krisantus Tri Pambudi Raharjo (Fakultas Pertanian, Universitas Timor, 2018)
Red beans are important legumes for human consumption and are considered a major source of vegetable protein for direct consumption. This study aimed to determine the effect of drought stress after the flowering period of red bean plants grown in entisol soil. The field trial was conducted from June to December 2017, in the experimental garden of the Faculty of Agriculture, University of Timor. Sasi Village, Kefamenanu City Subdistrict, TTU District, used a single factor Completely Randomized Design which was repeated 14 times. The factor applied is drought stress after the flowering period which consists of control (not stressed), 1 week after primordia without water, and 2 weeks after the flowering period without watering. Observations included air temperature, air humidity, soil moisture content, soil volume weight, plant height, leaf number, leaf area, canopy fresh weight, root fresh weight, plant fresh weight, canopy dry weight, root dry weight, plant-based dry weight, total dry weight, root canopy ratio, number of seeds per pod, number of pods per plant, dry seed weight per plant, harvest index. The results showed that drought stress after the primordial period or flowering of red beans had a negative influence on the red bean plants, resulting in failure of seed production.